Relationship between admission vitals and brain herniation in 32 cats: a retrospective study. Issue 8 (August 2022) - Her, Jiwoong; Merbl, Yael; Gerken, Katherine; Kim, Minjeong; Hofmeister, Erik; Bacek, Lenore M; Kuo, Kendon W; Yanke, Amy B
Objectives: The aim of the study was to evaluate whether any admission vitals correlated with the presence of brain herniation diagnosed via MRI in cats presenting with neurologic signs. Methods: Medical records at two veterinary university referral centers were reviewed to identify cats that underwent brain MRI between 2010 and 2019. A control group of cats with intracranial lesions without concurrent brain herniation was analyzed for comparison. Data relating to signalment, vitals on admission, abnormalities observed on initial neurologic examination, underlying etiology, advanced imaging findings and outcome were reviewed. A Modified Glasgow Coma Scale (MGCS) score was determined retrospectively based on initial neurologic examination. Logistic regressions were performed to investigate the relationship between each risk factor and the odds of brain herniation as diagnosed on MRI. Results: Thirty-two cats with brain herniation and 44 cats with abnormal brain MRI without evidence of herniation (as a control group) based on MRI findings were included. Cats with intracranial neoplasia vs other diagnoses were found to be at increased risk of herniation (odds ratio [OR] 4.8, 95% confidence interval [CI] 1.8–13.8; P = 0.001). The odds of herniation increased with age (OR 1.1, 95% CI 1.01–1.2; P = 0.031). Cats with herniation had a significantly lower level of consciousness in their MGCS score ( P <0.0001) than cats without herniation. There was no significant difference in either motor activity or brainstem reflexes between the groups ( P >0.05). Conclusions and relevance: Admission heart rate and blood pressure were not associated with brain herniation. Cats with herniation were presented with a significantly lower level of consciousness in their MGCS score; however, this clinical feature cannot be directly attributable to and predictive of herniation. Older cats with intracranial neoplasia are more likely to have brain herniation.